Analyse de la situation de l’environnement sanitaire des quartiers défavorisés dans le tissu urbain de Yopougon a Abidjan, Côte d’Ivoire - Kouassi Dongo; Fernand Koffi Kouamé; Brama Koné; Jean Biém; Marcel Tanner; Guéladio Cissé (VertigO)
The integration into a Geographical information system (GIS) of multi-source data from QUICKBIRD imagery, ancilliary data and the results from socio-environmental investigations allowed to analyse the sanitary environment of 6 precarious settlements located along an open and exposed drainage channel, in Yopougon (Abidjan, Côte d’Ivoire). The observatory of the sanitary environment of these deprivileged areas were conducted through analysis and mapping of main factors influencing the life quality of the populations. The spatial sharpness of QUICKBIRD imagery contributed to update the land use/land cover map. Analysis of various factors witch characterise the sanitary environment reveals many insufficiences as regards the management of the sanitation system of the settlements, thus exposing the populations to illness related to sanitation like malaria and diarrhoea. The findings will permit planing appropriate measurements to overcome sanitation problems in these precarious areas.